On horse-breaking - Moreton, Robert (Salt Lake City, UT : Project Gutenberg, 2023)
"On Horse-Breaking" by Robert Moreton is a practical guide on equine training written in the late 19th century. The work addresses common misconceptions and harsh methods traditionally used in horse-breaking, advocating instead for gentler, more effective techniques. Moreton aims to provide horse owners and agriculturists with insights that can help them enhance the value of their horses when properly trained. The opening of the treatise establishes the author's resolve to challenge brutish and outdated methods of haltering colts. Moreton recounts a vivid scene in which several men struggle unsuccessfully to halter a frightened colt using brute force, ultimately underscoring the need for a gentle and strategic approach. He contrasts this with his own successful technique, which involves calmness, patience, and the gradual building of trust between handler and horse. This method not only respects the animal's fear and instincts but sets the stage for successful training down the line. (This is an automatically generated summary.)
Release date is 2023-08-15
deaurider, David Wilson and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Horses -- Training; Horses